The Existence of Mekongga Customary Court in Resolving Crimes According to Kalosara Tolaki Mekongga Customary Law in Kolaka Regency - Hasdin Yadin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Customary Court is a court that applies the customary law system for indigenous people seeking justice through a deliberation mechanism. The existence of Customary Courts is not limited to the settlement of customary disputes, but also includes criminal cases. This raises three issues that must be reviewed, namely, how the existence of the Customary Court as an institution authorized by custom to examine and try criminal cases, as well as how the general public perceives the existence of the Court in resolving criminal cases. Using sociological and normative research methods, this study concludes that the limitations and forms of offenses formulated are limited to customary offenses that fall into the category of complaints and minor criminal cases. Then the existence of Customary Courts that cover minor crimes. Meanwhile, the general public has a perception that wants the existence of Customary Courts to be optimal because it prioritizes family deliberation which is a communal principle in customary law communities. This research suggests that there should be a uniformity of minor criminal cases that can be resolved by the Mekongga Customary Court through the Kalosara Tolaki Mekongga Customary Law Regulation in Kolaka district.